Processing Catfish Shreds For Economic Empowerment Of The Community In The Meruya Area, West Jakarta - Hidayah, Nurul; Asih, Daru; Andari, Putri (Jurnal Abdi Masyarakat (JAM), 2025)
This community service program aims to empower the economy of the residents of Meruya Selatan Village, West Jakarta, through training in processing catfish into shredded fish. This activity is designed to address the issues of low income and lack of food processing skills among the local PKK mothers. Through a series of training and mentoring sessions, this program will equip participants with skills in producing high-quality catfish floss, preservation techniques, packaging, and effective marketing strategies. The implementation methods include initial surveys, intensive training, hands-on practice, and continuous monitoring. Other targets include improving the knowledge and skills of participants, as well as expanding the marketing reach of catfish floss products. By utilizing local potential and appropriate technology, it is hoped that this program can increase family income, strengthen food security, and encourage local economic growth in Meruya Selatan Village. The PKM activities will conclude with a discussion session, a Q&A session, and the completion of a questionnaire. The outcomes of the PKM activities will be published in the form of mass media, articles, and journal publications.